Fatores comportamentais e cognitivos na aquisição de energia solar residencial - Cruz, Jonas da Costa (2024)
Green consumption is a way to reduce the negative impacts on the environment in the present and for future generations. In this context, renewable energies stand out due to the increasing residential electricity consumption. Solar energy systems, suitable for micro-scale electricity generation, reduce harmful waste and pollution from fossil fuel combustion. Furthermore, renewable technologies are becoming competitive in terms of cost savings. In this sense, studying Brazilian consumer behavior regarding the intention to adopt photovoltaic solar technology is significant. It is necessary to investigate the antecedents (mental accounting, regulatory focus, environmental awareness, and level of interpretation in the adoption of residential solar energy) that may lead consumers to environmental enthusiasm for pro environmental actions and, consequently, influence the adoption of solar energy. This study adopted a quantitative approach, using a survey method for descriptive purposes. The sample consisted of 556 Brazilian consumers from all regions of the country. Data analysis employed structural equation modeling and complementary analyses, including latent class analysis, importance-performance matrix analysis, and necessary condition analysis. The results revealed that variables such as mental accounting, regulatory focus, environmental awareness, social perception, and temporal perception are significant predictors of environmental enthusiasm, confirming previous studies. Environmental enthusiasm mediated the relationships between these variables and solar energy adoption, standing out as an internal value that stimulates sustainable behavior. The heterogeneity analysis of respondents identified two distinct groups. In Group 1, mental accounting and environmental awareness significantly impacted environmental enthusiasm, while temporal perception was more relevant in Group 2. Social perception was significant in both groups. Regulatory focus (prevention and promotion) and geographical perception did not significantly affect either group. Regarding indirect effects, the mediation of environmental enthusiasm between mental accounting and solar energy adoption was significant only in Group 1. The same dynamics were observed in the relationship between environmental awareness and solar energy adoption and between social perception and solar energy adoption, reinforcing the importance of intrinsic values in this group. On the other hand, enthusiasm did not significantly mediate the relationships with geographical and temporal perception in any of the analyzed segments.